1995
DOI: 10.2151/jmsj1965.73.2b_471
|View full text |Cite
|
Sign up to set email alerts
|

Dual Doppler Radar Observation of a Tropical Rainband Developed from Two Convective Clouds

Abstract: The structure and evolution of a small, isolated convective rainband, which developed over the warm pool between January 5 and 6, 1993, were examined in detail using sounding and dual-Doppler radar data from Manus Island, Papua New Guinea, during the TOGA-COARE TOP. The rainband developed from two small convective cells and decayed within the dual-Doppler radar coverage area.The rainband was oriented parallel to the low-level environmental shear with a lower magnitude of 2.5 x 10-3 s-1 and the CAPE was as smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Cloud clusters are a common tropical cloud system (Leary and Houze 1979;Houze and Betts 1981;Takayabu and Murakami 1991;Mori 1992Mori , 1995Satoh et al 1995;Chen et al 1996;Houze et al 2000). Studies using data from the Global Atmospheric Research Program's (GARP) Atlantic Tropical Experiment (GATE) showed that a CC is comprised of cloud systems organized on the mesoscale with a horizontal scale of O(10 km) and a lifetime of several to ten hours (e.g., Zipser 1969Zipser , 1977Houze 1977; Leary and Houze 1979;Zipser et al 1981;Mori 1992Mori , 1995Satoh et al 1995;Fujiyoshi and Geng 1995;Takahashi and Uyeda 1995;Chen et al 1996;Houze et al 2000). A variety of terms have been used to define various mesoscale cloud systems, such as mesoscale precipitating feature (MPF; Leary and Houze 1979), mesoscale convective system (MCS; Houze 1993, p. 334), rainband, squall line, and sometimes cloud cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud clusters are a common tropical cloud system (Leary and Houze 1979;Houze and Betts 1981;Takayabu and Murakami 1991;Mori 1992Mori , 1995Satoh et al 1995;Chen et al 1996;Houze et al 2000). Studies using data from the Global Atmospheric Research Program's (GARP) Atlantic Tropical Experiment (GATE) showed that a CC is comprised of cloud systems organized on the mesoscale with a horizontal scale of O(10 km) and a lifetime of several to ten hours (e.g., Zipser 1969Zipser , 1977Houze 1977; Leary and Houze 1979;Zipser et al 1981;Mori 1992Mori , 1995Satoh et al 1995;Fujiyoshi and Geng 1995;Takahashi and Uyeda 1995;Chen et al 1996;Houze et al 2000). A variety of terms have been used to define various mesoscale cloud systems, such as mesoscale precipitating feature (MPF; Leary and Houze 1979), mesoscale convective system (MCS; Houze 1993, p. 334), rainband, squall line, and sometimes cloud cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The 5J (5 January) case is that of an echo merging, evolved under a relatively stable condition by taking a long time (about three hours) for a small echo to reach to the maximum echo area (810km2). Fujiyoshi and Geng (1995) described the development process of this echo. The 16D(a) (First line echo of 16 December) and 16D(b) (Second line echo of 16 December) are squall-line-like echoes developed successively in the southeast and northwest of Manus.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the warm-rain process in squall lines at Darwin, Australia, was discussed by Keenan and Rutledge (1993). As an example of a simple case of cloud development, Fujiyoshi and Geng (1995) analyzed an isolated convective echo over the sea (5 January case) and described the process and mechanism of the merging effect of clouds for development in a relatively stable condition. At the beginning stage of the cloud cluster development, the warm-rain process dominated.…”
Section: Discussionmentioning
confidence: 99%
“…7b. Fujiyoshi et al (1994) had supposed that such enhancements of echo intensity were caused by coalescence growth taking place, namely, the "warm-rain mechanism". The results of the present work show simultaneous measurements of an increase in frequencies around 1.0mm in diameter on the size distribution of raindrops in Fig.…”
Section: Applications For Analyses Of Radar Datamentioning
confidence: 99%